Lignocellulosic Bionanomaterials for Biosensor Applications - Ekrem Durmaz; Selva Sertkaya; Hande Yilmaz; Cagri Olgun; Orhan Ozcelik; Ayhan Tozluoglu; Zeki Candan (Micromachines, 2023)
The rapid population growth, increasing global energy demand, climate change, and excessive use of fossil fuels have adversely affected environmental management and sustainability. Furthermore, the requirements for a safer ecology and environment have necessitated the use of renewable materials, thereby solving the problem of sustainability of resources. In this perspective, lignocellulosic biomass is an attractive natural resource because of its abundance, renewability, recyclability, and low cost. The ever-increasing developments in nanotechnology have opened up new vistas in sensor fabrication such as biosensor design for electronics, communication, automobile, optical products, packaging, textile, biomedical, and tissue engineering. Due to their outstanding properties such as biodegradability, biocompatibility, non-toxicity, improved electrical and thermal conductivity, high physical and mechanical properties, high surface area and catalytic activity, lignocellulosic bionanomaterials including nanocellulose and nanolignin emerge as very promising raw materials to be used in the development of high-impact biosensors. In this article, the use of lignocellulosic bionanomaterials in biosensor applications is reviewed and major challenges and opportunities are identified.